Evaluation of the QIAstat-Dx Respiratory SARS-CoV-2 Panel, the First Rapid Multiplex PCR Commercial Assay for SARS-CoV-2 Detection - Visseaux, Benoit (J Clin Microbiol, 2020)
In the race to contain severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), efficient detection and triage of infected patients must rely on rapid and reliable testing. In this work, we performed the first evaluation of the QIAstat-Dx respiratory SARS-CoV-2 panel (QIAstat-SARS) for SARS-CoV-2 detection. This assay is the first rapid multiplex PCR (mPCR) assay, including SARS-CoV-2 detection, and is fully compatible with a non-PCR-trained laboratory or point-of-care (PoC) testing. This evaluation was performed using 69 primary clinical samples (66 nasopharyngeal swabs [NPS], 1 bronchoalveolar lavage fluid sample [BAL], 1 tracheal aspirate sample, and 1 bronchial aspirate sample) comparing SARS-CoV-2 detection with the currently WHO-recommended reverse transcription-PCR (RT-PCR) (WHO-RT-PCR) workflow. Additionally, a comparative limit of detection (LoD) assessment was performed for QIAstat-SARS and WHO-RT-PCR using a quantified clinical sample. Compatibility of sample pretreatment for viral neutralization or viscous samples with the QIAstat-SARS system were also tested. The QIAstat-Dx respiratory SARS-CoV-2 panel demonstrated a sensitivity comparable to that of the WHO-recommended assay with a limit of detection at 1,000 copies/ml. The overall percent agreement between QIAstat-Dx SARS and WHO-RT-PCR on 69 clinical samples was 97% with a sensitivity of 100% (40/40) and specificity at 93% (27/29). No cross-reaction was encountered for any other respiratory viruses or bacteria included in the panel. The QIAstat-SARS rapid multiplex PCR panel provides a highly sensitive, robust, and accurate assay for rapid detection of SARS-CoV-2. This assay allows rapid decisions even in non-PCR-trained laboratory or point-of-care testing, allowing innovative organization.